Enhanced State-of-Charge Balancing Control for MMC-SCES Using Centralized Controllers and Adaptive Optimization - Qiluan Yang; Huangqing Xiao; Qionghai Zhu (Applied Sciences)
The modular multilevel converter with embedded supercapacitor energy storage system (MMC-SCES) is a promising solution to the integration challenges posed by large-scale renewable energy. However, inconsistencies in supercapacitor characteristics across energy storage submodules (ESMs) can lead to state-of-charge (SOC) imbalances, reducing overall energy storage utilization. To address this challenge, this paper proposes an enhanced SOC balancing control strategy that leverages the inherent correlation between SOC and submodule capacitor voltage. The strategy simultaneously regulates both energy storage power and ESM capacitor voltage to maintain balance. A two-terminal transmission system with MMC-SCES is built in PSCAD/EMTDC. The results demonstrated that the proposed strategy achieved SOC balancing with only six centralized energy storage controllers, while the SOC balancing of the ESMs remained independent of the startup time. The implementation of the reduced switching frequency voltage balancing algorithm reduced the average switching frequency by 94.54% while maintaining the maximum SOC difference below 0.50%. Moreover, the adaptive coefficients improved the balancing speed by approximately 15% and reduced the initial circulating current by approximately 25%.